A polyphasic approach leading to the discovery of new taxa of terrestrial cyanobacteria for the flora of Ukraine - Mikhailyuk, T.I.; Vinogradova, O.M.; Gromakova, A.B.; Glaser, K.; Karsten, U. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2023)
Several morphotypes of filamentous cyanobacteria were found in the terrestrial habitats of the Kharkiv Region (biological soil crusts) and in the vicinity of Kyiv (old concrete wall in the forest). Morphological and molecular characterization of four original strains revealed that they belong to recently described genera Wilmottia Strunecký, Elster et Komárek, Pycnacronema M.D. Martins et Branco, Myxacorys Pietrasiak et J.R. Johansen and Tildeniella Mai, J.R. Johansen et Pietrasiak. All of them are new to the flora of Ukraine. Besides the analysis of p-distances, the nucleotide sequence of the 16S-23S ITS region and the secondary structures of its most informative helices, we used in our phylogenetic analyses sequences of the 16S rRNA gene. All Ukrainian strains joined the clades of the corresponding genera with a high degree of support in the Bayesian and Maximum Likelihood analyses. However, their species-level identification gave ambiguous results. Reliable result was obtained only for the strain of genus Wilmottia. It was identified as Wilmottia murrayi (W. et G.S.West) Strunecký, Elster et Komárek. This is the first morphologically and molecularly confirmed record of this species in Europe. Two strains were identified as Pycnacronema cf. caatingensis and Tildeniella cf. torsiva due to their deviations from these species both in morphology and the 16S–23S ITS secondary structures. In the 16S rRNA gene–based phylogenetic analysis, original strain of the genus Myxacorys took separate position among the known species of this genus and also had a number of morphological differences from them. Therefore, it might represent a new species, but this cannot be proven due to the lack of a 16S-23S ITS sequence of the original strain. Detailed description of morphology of the studied strains with tabular review of corresponding species are given.